Microsatellite markers for assessing genetic purity of hybrid seed in sorghum - K. SUDARSHAN PATIL; J. SURESH; M. PRAVEEN; G. ANURAG UTTAM; VILAS A. TONAPI; J.V. PATIL; R. MADHUSUDHANA (Seed Research, 2026)
Genetic purity of sorghum hybrid seed is tested conventionally through Grow-out-test (GOT) involving morphological descriptors, which is costly and time consuming. The utility of microsatellite (SSR) markers for analyzing the genetic purity involving three sorghum hybrids was verified. Field grown four-hundred hybrid plants were examined for purity involving morphological descriptors and with selected SSR markers. SSR assay confirmed the impure hybrids identified through GOT with banding pattern suggesting the impure plants could be from A x B seed and seed of R parent. Compared to GOT, levels of genetic purity of seed lots assessed with markers was slightly less indicating greater ability and precision of markers in identifying impure plants. The study showed that SSR markers are efficient to test genetic purity of sorghum hybrid seed, and can be safely employed to replace GOT for making quick and timely decisions for marketing of hybrid seeds in the following crop season.